Improved Survival in a Cohort of Patients Aged 75 Years and Older With Fecal Immunochemical Testing–Detected Colorectal Cancer. Issue 4 (28th June 2022) - Cahill, Caitlin; Lipson, Mark E.; Afzal, Arfan R.; Maclean, Anthony R.; Wong, Clarence K.; Roen, Sharla; Buie, W. Donald
Abstract : BACKGROUND: Fecal immunochemical testing is an accepted form of colorectal cancer screening and is recommended for adults up to the age of 75 years in Canadian guidelines. However, many individuals 75 years and older continue to receive fecal immunochemical testing despite being outside accepted guidelines. OBJECTIVE: This study aimed to determine whether patients aged 75 years and older with screen-detected cancer demonstrated improved outcomes and survival compared with patients with non–screen-detected cancer. DESIGN: This is a retrospective population-based cohort study. SETTINGS: Provincial data were collected from the Alberta Cancer Registry and the Alberta Colorectal Cancer Screening Program between November 2013 and 2019. PATIENTS: We identified an aggregated patient cohort aged 75 years and older with a diagnosis of colorectal cancer from November 2013 to November 2019, as well as patients 75 years and older who underwent fecal immunochemical testing within these dates. MAIN OUTCOME MEASURES: The proportion of screen-detected colorectal cancers was calculated. Surgical intervention, hospital length of stay, postoperative mortality, and overall survival were analyzed. RESULTS: Between November 2013 and 2019, 3586 patients 75 years and older were diagnosed with colorectal cancer; 690 (19%) were "screen-detected." Screen-detected patients were almost 3 times more likely to undergo surgery (OR, 2.83) and had a 36% overall survival benefit (HR, 0.64) compared with non–screen-detected patients, adjusted for other variables such as age, Charlson Comorbidity Index, and stage. LIMITATIONS: The retrospective study design prevents conclusions regarding causation. CONCLUSIONS: Screen detection of colorectal cancer in patients aged 75 years and older is associated with improved overall survival when controlling for other potential confounders. When compared with their non–screen-detected counterparts, these patients have an earlier stage of disease and are more likely to undergo surgical intervention with improved outcomes, irrespective of age. These data may support screening for appropriately selected patients who would otherwise fall outside of current guidelines. See Video Abstract at http://links.lww.com/DCR/B986 . SOBREVIDA MEJORADA EN UNA COHORTE DE PACIENTES DE 75 AÑOS O MÁS CON CÁNCER COLORRECTAL DETECTADOS POR RIF: ANTECEDENTES: La prueba basada en una Reacción Inmunoquímica Fecal - RIF, es una forma aceptada de detección de cáncer colorrectal y esta recomendada en adultos a partir de los 75 años en las guías canadienses. Sin embargo, muchas personas de 75 años o más continúan realizándose pruebas inmunoquímicas fecales a pesar de estar fuera de las guías aceptadas. OBJETIVO: Poder determinar si los pacientes de 75 años o más con detección RIF positiva a un cáncer demuestran mejores resultados y sobrevida comparados con los pacientes sin detección. DISEÑO: Estudio de cohortes retrospectivo basado en una población definida. CONFIGURACIÓN: Se recopilaron los datos provinciales del Registro de cánceres y del Programa de detección de cáncer colorrectal de Alberta, Canada, entre 2013 y 2019. PACIENTES: Identificamos una cohorte agregada de pacientes de 75 años o más con diagnóstico de cáncer colorrectal desde noviembre de 2013 hasta noviembre de 2019, así como pacientes de 75 años o más que se sometieron a pruebas inmunoquímicas fecales dentro de las fechas mencionadas. PRINCIPALES MEDIDAS DE RESULTADO: Se calculó la proporción de cánceres colorrectales detectados mediante un cribado. Se analizaron la intervención quirúrgica, la duración de la estadía hospitalaria, la mortalidad post-operatoria y la sobrevida global. RESULTADOS: Entre noviembre de 2013 y noviembre 2019, 3586 pacientes de 75 años o más, fueron diagnosticados con cáncer colorrectal; 690 (19%) fueron detectados por cribado. Los pacientes detectados mediante el cribado, tenían casi tres veces más probabilidades de someterse a una cirugía (Razón de Probabilidad de 2, 83) y beneficiaron de una sobrevida general del 36 % (HR 0, 64) comparados con los pacientes sin detectación por cribado, corregidos por otras variables como la edad, el índice de comorbilidad de Charlson y el estadío del tumor. LIMITACIONES: El diseño retrospective del presente estudio impide obtener conclusiones con respecto a la causalidad. CONCLUSIONES: La detección por cribado de cáncer colorrectal en pacientes de 75 años o más se asocia con una mejor sobrevida general cuando se controlan los otros posibles factores de confusión. Comparando con las contrapartes no detectadas por cribado, estos pacientes se encuentran en una etapa más temprana de la enfermedad y es más probable que se sometan a una intervención quirúrgica con mejores resultados, independientemente a la edad. Estos datos pueden respaldar la detección de pacientes adecuadamente seleccionados que, de otro modo, quedarían fuera de las pautas actuales. Consulte Video Resumen en http://links.lww.com/DCR/B986 . (Traducción—Dr. Xavier Delgadillo )